Mannequin‐based Telesimulation: Increasing Access to Simulation‐based Education. (4th October 2017) - Hayden, Emily M.; Khatri, Avni; Kelly, Hillary R.; Yager, Phoebe H.; Salazar, Gloria M.
Abstract: A telesimulation platform utilizes communications technology to provide mannequin‐based simulation education between learners and instructors located remotely from one another. Specifically, the instructor controls the mannequin and moderates the debriefing remotely. During these sessions, the instructor observes the learners in real time and provides immediate feedback during the debriefing. This platform obviates the need to have instructors, learners, and mannequins in the same place at the same time, potentially allowing simulation‐based educational sessions to occur with greater frequency for institutions not located proximate to formal simulation centers. Additionally, the telesimulation platform enables an experienced simulation instructor to observe and directly help new simulation instructors at remote simulation locations. Readily available Web‐conferencing, screen‐sharing software, microphones, and webcams makes telesimulation possible. Mannequin‐based telesimulation is relatively new and not well represented in the literature, but could facilitate systems changes, providing educational experiences to health care professionals in locations not currently benefiting from mannequin‐based simulation opportunities. Several research questions need to be addressed in future studies to better develop this educational approach, including technical feasibility, logistic issues, a comparison of telesimulation to other simulation approaches, and assessing limitations of the telesimulation platform.